Evaluation of the Safin Pati Sports School Sports Achievement Development Program in Pati Regency in 2023 - Hanif Putra Pamungkas; Nasuka; Hadi (Universitas Negeri Semarang, 2024)
Football achievement coaching programs need to be evaluated comprehensively to ensure the effectiveness and efficiency of their implementation. This research aims to evaluate the Safin Pati Sports School Sports Achievement Development Program in Pati Regency in 2023 through CIPP evaluation. CIPP program evaluation is often used in sports achievement coaching. At the context stage, the evaluation of the CIPP sports achievement coaching program includes an analysis of environmental conditions that affect the implementation of the program. The research method used in this study uses a qualitative approach with data collection techniques including observation, interviews and documentation as well as the validity of the data. The results of the study obtained information that the Safin Pati Sports School (SPSS) organization has a clear and measurable vision, mission and objectives of the prestige coaching program. Human resources at Safin Pati Sports School (SPSS) are well indicated in terms of the athlete recruitment system with applicable conditions and coach recruitment with certain criteria. The training program implemented by Safin Pati Sports School (SPSS) went well. The facilities and infrastructure owned by Safin Pati Sports School (SPSS) are said to be good and complete. Findings in the field show that the source of funds for Safin Pati Sports School (SPSS) comes from social funds and the academy itself. It is hoped that the management and pelath can continue and maintain a well-programmed comprehensive football sports performance coaching program. The management of Safin Pati Sports School (SPSS) must further improve its coordination and relationship with Koni, the provincial government or the central government in order to make a contribution that results in limited opportunities for athletes to compete so that the achievements obtained are according to the opportunity to compete only.